Liaison Psychiatry in a Tertiary Care Hospital: Experience of the “20 de Noviembre” National Medical Center - Moya Sánchez, Deldhy Nicolas; Meneses-Luna, Oscar; Ochoa Madrigal, Marta Georgina; Espinoza de Avila, Elia Francisca; Cruz Aviña, Francisco Javier; Salazar-Rodriguez, Alejandro; Sanchez-Hernandez, Laura Kristel; Mendez Zamora, Jesus (Psychosomatic Medicine and General Practice, 2025)
Introduction. Liaison Psychiatry is a key subspecialty in the comprehensive management of hospitalized patients in general hospitals. Its implementation at the Centro Médico Nacional 20 de Noviembre has enabled the approach to medical-psychiatric comorbidity within a biopsychosocial framework. Objective. To describe the development, current structure, and outcomes of the Liaison Psychiatry Service at the CMN 20 de Noviembre. Methods. Descriptive retrospective study based on institutional documentation and service statistics from recent years. Results. The article presents the historical background of the service, the current care model, and the most frequent diagnoses handled through consultations. The clinical, academic, and organizational benefits of integrating mental health in a tertiary care hospital are highlighted. Conclusions. The experience of CMN 20 de Noviembre confirms the importance of Liaison Psychiatry in providing comprehensive patient care, strengthening the doctor-patient relationship, and optimizing hospital resources. Key words: Tertiary Care Hospital, Liaison Psychiatry, Mental Health Integration